TEACHING TECHNIQUES OF ENGLISH (ISLAMIC) VOCABULARY FOR HADITH STUDENTS IN STAIN MANDAILING NATAL - Sri Wahyuni Hasibuan (Journal of English Education and Linguistics, 2021)
The purpose of this study was to describe the types of technique used by lecturer in teaching English Islamic vocabulary and to know the reasons of technique used by lecturer in teaching English Islamic vocabulary in 2021/2022 academic year in 1st semester. The study used descriptive qualitative research. The data obtained to answer the types of techniques was based on observation and the data to answer the reasons of techniques was interview transcription. Data were analyzed by data reduction, data display and data verification. The data from the observations were analyzed and the data from the interviews were transcribed. The results was there are three types of techniques used by lecturer in teaching English Islamic vocabulary. They are visual technique (using picture), verbal technique (meaning definition, translation, and memorization), and technique of teaching (repetition drill). There are some reasons used by lecturer in teaching English Islamic vocabulary among them are saving time, to make student happy and not bored, gives long term memory retention to the learners etc.